Association of common bacterial blight (Xanthomonas axonopodis pv. phaseoli) epidemics with agro ecological factors in Southwestern Ethiopia (International Journal of Agricultural Research, Innovation and Technology, 2021)
Common bacterial blight, caused by Xanthomonas axonopodis pv. phaseoli, is an economically important disease of common bean and causes significant yield losses in Ethiopia. A field survey was conducted to understand the spatial distribution, relative importance and association of common bacterial blight epidemics with agro-ecological factors in low and mid-land areas of Southwestern, Ethiopia, during the 2018-19 cropping season. A total 85 bean fields were assessed in four common bean growing districts. High diseases incidence and severity was recorded at Debub Ari (77.6 and 52.7%, respectively) while the lowest was from Male (38.5 and 28.0%, respectively). The associations between disease parameters and agro-ecological factors were analyzed using multiple logistic regression models. Agronomic practices including NPS fertilization, preceding crop, weed management and plant population had highly significant (P